Thoughts On The New Dadaist Tactic Of Our Era: ‘Sweded Films' And Michel Gondry's Be Kind Rewind - Aytemiz, Pelin (The Turkish Online Journal of Design Art and Communication, 2016)
Be Kind Rewind (2008), comedy-drama film written and directed by Michel Gondry, can be considered as an alternative film as it has initiated a novel and subversive cultural practice called “sweding”. Sweding, initially a term used by the characters of the film that describes their amateur way of remaking the famous cult films, started to be a marginal phenomena and adopted by crowds as a tactic of subverting dominant ideologies of mass culture. The meaning of sweding cut across its original meaning as a way of producing homemade films and started to be described as any kind of practice of re-creating something from scratch using commonly available, mundane everyday objects and skills. This idea of remaking has a critical and subversive potential. In this sense, this paper aims to engage in a critical analysis of Be Kind Rewind's ability to shift meanings of filmmaking using the criticism of Collin McCabe's “Classical Realist Text'” and trace the subversive and alternative elements of this cultural phenomenon of sweding. It will be argued that the style and amateur film production associated with sweded films recall the techniques of the 20th-century art movement Dadaism that questions art and comments on daily life practices. Departing from this observation, the paper will open up the new “genre” of “Sweded Cinema” to further questioning and suggest that there is a potential in Sweded Cinema in challenging Classical Hollywood Cinema just like the way Dadaism countered high art and dominant ideologies of its time.
Keywords: visual culture; sweding; everyday life; Michel Gondry; dada; remake; genre; görsel kültür; sweding; gündelik hayat; yeniden üretim; tür